The influence of social media marketing, brand image, and perceived value on consumer purchase intention - Margaretha Ardhanari; Sebastiana Viphindrartin (Faculty of Economics and Business, University of Muhammadiyah Malang, 2026)
This study examines the influence of social media marketing on purchase intention, with brand image and perceived value as mediating variables. Grounded in Uses and Gratifications Theory and Signaling Theory, the research adopts a quantitative approach using PLS-SEM on data collected from 150 Indonesian social media users. The results show that social media marketing significantly affects brand image and purchase intention, both directly and indirectly through perceived value. Perceived value emerges as the strongest predictor of purchase intention, followed by brand image. These findings highlight the strategic role of social media engagement in building reputational capital and enhancing consumer value perception. The study provides managerial implications for optimizing digital marketing strategies through trust-building, influencer engagement, and value creation in emerging markets.